PENGEMBANGAN E-MODUL UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL DAN KEMANDIRIAN BELAJAR PADA MATERI PERSAMAAN TRIGONOMETRI - Yuni Fitriwanti; Dede Suratman; Nilamsari Kusumastuti; Dona Fitriawan (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to develop e-modules that can increase independence and understanding of concepts in learning trigonometric equations for students of Class XI MIA SMA Negeri 1 Sungai Raya. The 4-D development method (Four-D Model) used consists of four phases: definition, design, development, and deployment. The aim of this research is to develop e-modules that can increase independence and conceptual understanding in learning trigonometry equations for Class XI MIA students at SMA Negeri 1 Sungai Raya. The 4-D development model (Four-D Model) used consists of four phases: definition, design, development, and deployment. This research produced an e-model of trigonometry equation material that is valid, practical and can increase students' independence and understanding of concepts. The results of testing the understanding of the material concept of trigonometry equations average pretest 52.21 and posttest 84.85. This is also supported by the acquisition of a calculated score of 0.68 ?0.7. This means they have a better understanding of trigonometry equations. The results of the analysis of the level of learning independence of students obtained an independence level of 81.27%. The average score obtained is 81.27%, and the data shows that the independent learning of students goes well when learning with the developed e-modules. This research produced a product in the form of an e-module of trigonometry equations which was developed to help improve conceptual understanding of teaching materials and to increase students' independence in learning.Pengembangan e-modul yang dapat meningkatkan kemandirian dan pemahaman konsep dalam belajar persamaan trigonometri peserta didik Kelas XI MIA SMA Negeri 1 Sungai Raya merupakan tujuan dari penelitian ini. Model pengembangan 4-D (Model Empat-D) yang digunakan terdiri dari empat fase: definisi, desain, pengembangan, dan penyebaran. Penelitian ini menghasilkan e-model materi persamaan trigonometri yang valid, praktis serta dapat meningkatkan kemandirian dan pemahaman konsep peserta didik. Hasil pengujian pemahaman konsep materi persamaan trigonometri rata-rata pretest 52,21 dan postest 84,85. Hal ini juga didukung dengan perolehan skor hitung sebesar 0,68 0,7. Ini berarti pemahaman yang lebih baik tentang persamaan trigonometri dimiliki oleh mereka. Hasil analisis tingkat kemandirian belajar peserta didik diperoleh tingkat kemandirian sebesar 81,27%. Rata-rata skor yang diperoleh adalah 81,27%, dan data tersebut menunjukkan bahwa kemandirian belajar peserta didik berjalan baik ketika belajar dengan e-modul yang dikembangkan. Penelitian ini menghasilkan produk berupa e-modul persamaan trigonometri yang dikembangkan guna membantu meningkatkan pemahaman konseptual materi ajar dan dapat meningkatkan kemandirian peserta didik dalam belajar.